2015
DOI: 10.1371/journal.pone.0120809
|View full text |Cite
|
Sign up to set email alerts
|

De Novo RNA Sequencing and Transcriptome Analysis of Colletotrichum gloeosporioides ES026 Reveal Genes Related to Biosynthesis of Huperzine A

Abstract: Huperzine A is important in the treatment of Alzheimer’s disease. There are major challenges for the mass production of huperzine A from plants due to the limited number of huperzine-A-producing plants, as well as the low content of huperzine A in these plants. Various endophytic fungi produce huperzine A. Colletotrichum gloeosporioides ES026 was previously isolated from a huperzine-A-producing plant Huperzia serrata, and this fungus also produces huperzine A. In this study, de novo RNA sequencing of C. gloeos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…Similar fi ndings have been reported in the case of huperzine A producing endophytes. Their fungal amine oxidase genes have been found to present low similarities to the corresponding plant genes, and only conserved consensus sequences were present by the fungal and plant functional amine oxidase proteins Zhang et al, 2015), which supports the co-evolution theory rather than the HGT theory. This has been well established in the case of gibberellin biosynthetic pathways in fungi and higher plants where diff erences in genes and enzymes indicated converged evolution of GA metabolic pathways (Böm-ke and Tudzynski, 2009).…”
Section: Miquelia Dentatamentioning
confidence: 70%
“…Similar fi ndings have been reported in the case of huperzine A producing endophytes. Their fungal amine oxidase genes have been found to present low similarities to the corresponding plant genes, and only conserved consensus sequences were present by the fungal and plant functional amine oxidase proteins Zhang et al, 2015), which supports the co-evolution theory rather than the HGT theory. This has been well established in the case of gibberellin biosynthetic pathways in fungi and higher plants where diff erences in genes and enzymes indicated converged evolution of GA metabolic pathways (Böm-ke and Tudzynski, 2009).…”
Section: Miquelia Dentatamentioning
confidence: 70%
“…As a newly explored biological resource, endophytic fungi offer an excellent opportunity to produce active compounds without the same limitations as plant resources. However, critical obstacles such as low and unstable production of metabolites greatly inhibit the application of these fungi (Zhang et al, 2015 ). Understanding the biosynthesis pathway and relative key genes is essential for an intensive control of their viability and stability.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, transcriptome sequencing is an effective approach for mining genetic information from unknown genome sequences, and is useful in gene sequencing, new gene discovery, and studying gene regulation (Wang et al, 2009 ). This method can produce millions of short cDNA reads and provide useful information on gene expression, based on RNA abundance (Peng et al, 2014 ; Zhang et al, 2015 ). Next-generation sequencing technologies such as Roche 454 and Illumina RNA-Seq have emerged during a golden age of scientific discovery (Margulies et al, 2005 ; Metzker, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, they obtained RNA from this strain for sequencing analysis and individually validated the expression of copper amine oxidase (CAO) in the roots, stems, and leaves of H. serrata. They found that CAO may participate in HupA biosynthesis and may play a crucial role in regulating HupA yield in ES026 [9] . In 2017, Yang et al reported the transcriptome analysis of four different H. serrata tissues (roots, stems, leaves, and sporangias) and identified LDC, CAO, and PKS in transcripts [10] .…”
Section: Introductionmentioning
confidence: 99%